2021
DOI: 10.3389/fneur.2021.631227
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Low-Density Lipoprotein Cholesterol and Platelet Distribution Width in Acute Ischemic Stroke

Abstract: Objective: Elevated low-density lipoprotein cholesterol (LDL-C) is an established risk factor for ischemic stroke; however, whether LDL-C affects the platelet deformation function in the peripheral blood circulation in patients with acute ischemic stroke (AIS) is unknown. The present study aimed to investigate the relationship between LDL-C and platelet distribution width (PDW) in AIS patients.Methods: We conducted a cross-sectional hospitalized-based study of consecutive 438 patients with AIS within 24 h. Blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
0
6
1
Order By: Relevance
“…However, due to the existence of clinical interfering factors such as exogenous PLT supplementation and blood dilution, the accuracy of PLT in predicting the prognosis of severe burns is questionable. Platelet index, such as PDW and PPR (a derivative indicator of CBC), could be used together with PLT to assess the severity of various diseases, rather than relying solely on PLT ( 15 , 25 27 ). In this study, we here in first found that PDW and PPR at 3 and 7 days postburn were independent risk factors for 120-day mortality in severe burn patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, due to the existence of clinical interfering factors such as exogenous PLT supplementation and blood dilution, the accuracy of PLT in predicting the prognosis of severe burns is questionable. Platelet index, such as PDW and PPR (a derivative indicator of CBC), could be used together with PLT to assess the severity of various diseases, rather than relying solely on PLT ( 15 , 25 27 ). In this study, we here in first found that PDW and PPR at 3 and 7 days postburn were independent risk factors for 120-day mortality in severe burn patients.…”
Section: Discussionmentioning
confidence: 99%
“…The PDW-to-PLT ratio (PPR) seems more interesting and valuable. The prognostic values of PDW and PPR have been confirmed in a variety of disease states, except for severe burn injury (15–17). In the early stages of burn injury, PLT activation and increased aggregation lead to a large consumption of PLT, and fluid resuscitation leads to blood dilution, leading to a progressive decrease in circulating PLT (18, 19).…”
Section: Introductionmentioning
confidence: 95%
“…Recently, the association between PDW and diverse diseases, including metabolic diseases, has gained increasing attention (49). PDW is often used to estimate platelet volume heterogeneity, and the elevated PDW is highly suggestive that platelet volume is heterogeneous (50). There are even reports indicating that PDW may be more sensitive than MPV in reflecting platelet activation (51,52).…”
Section: Madan Et Al Conducted a Meta-analysis Based On 8 Studies On ...mentioning
confidence: 99%
“…Previous studies have indicated that MPV may serve as an independent risk factor for the onset of stroke (10,11). Additionally, some studies have also revealed a potential correlation between cerebral infarction and reduced PLT levels as well as elevated PDW levels (12)(13)(14). However, the current research on the impact of PCT on stroke has been scarcely reported.…”
Section: Introductionmentioning
confidence: 99%